2014
DOI: 10.3892/mmr.2014.2415
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal nitric oxide synthase, as a downstream signaling molecule of c-jun, regulates the survival of differentiated PC12 cells

Abstract: The high expression of c-jun and neuronal nitric oxide synthase (nNOS) generally occurs in neurons following the generation of various animal models of central neuronal diseases. However, the mechanism between them in neuronal disease remains to be elucidated. Our previous studies demonstrated that the expression of c‑jun always occurs prior to expression of nNOS in motoneuron injuries and suppression of c‑jun expression by c‑jun siRNA decreased nNOS expression in differentiated PC12 cells. The present study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…NeuN is a transcription factor, participating in the biochemical process of the proteins, which is expressed in the nucleus and cytoplasm in the healthy mature neurons (Mullen et al 1992 ). Under the pathological conditions that are fatal to the neurons such as in BPRA, cerebral ischemia, and hypoxia and trauma, the NeuN immunoreactivity has been reported to decrease in the injured neurons (Igarashi et al 2001 ; Davoli et al 2002 ; Cheng et al 2014 ; Cui et al 2014 ). The injury-induced loss of NeuN immunoreactivity has been considered to be due to the depletion of NeuN protein or loss of its antigenicity (McPhail et al 2004 a, b; Unal-Cevik et al 2004 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NeuN is a transcription factor, participating in the biochemical process of the proteins, which is expressed in the nucleus and cytoplasm in the healthy mature neurons (Mullen et al 1992 ). Under the pathological conditions that are fatal to the neurons such as in BPRA, cerebral ischemia, and hypoxia and trauma, the NeuN immunoreactivity has been reported to decrease in the injured neurons (Igarashi et al 2001 ; Davoli et al 2002 ; Cheng et al 2014 ; Cui et al 2014 ). The injury-induced loss of NeuN immunoreactivity has been considered to be due to the depletion of NeuN protein or loss of its antigenicity (McPhail et al 2004 a, b; Unal-Cevik et al 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…The correlation of the expressions between ATF-3 and nNOS in the present study was similar to that between the phospho-c-jun and nNOS in the previous studies (Wang et al 2011 ; Li et al 2015 ). The phosphorylation of the c-jun in the BPRA-injured motoneurons was demonstrated to contribute to the death of the injured motoneurons and also thought to regulate the downstream nNOS gene expression in BPRA-injured motoneurons (Yuan et al 2010 ; Cheng et al 2013 , 2014 ). Furthermore, previous study has found that a function of ATF-3 in neurons under death stress, just like the spinal motoneurons under root avulsion in the present study, is to inhibit the mitogen-activated kinase kinase kinase 1 (MEKK1)—c-jun N-terminal kinase (JNK)-induced apoptosis (Nakagomi et al 2003 ; Greer et al 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, AP-1 induction by high-intensity light was previously observed not only in wild-type animals, but also in the phenotypes lacking GRK1 or arrestin (Hao et al, 2002). AP-1 can activate downstream pro-apoptotic proteins, such as nNOS that can be upregulated by c-jun, a component of AP-1 complex (Cheng et al, 2014). Upregulation of nNOS and NO-sensitive guanylate cyclase would further increase calcium influx into the photoreceptors through cGMP-gated channels and promote their apoptosis through mitochondrial depolarization and, likely, activation of Ca 2+ -dependent endonucleases (Donovan et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The preservation of synaptic boutons by 7-nitroindazole or SP600125 treatment suggests that nitric oxide suppression offered protection from synaptic withdrawal. C-Jun is a major subunit of Activator protein 1 (AP-1) transcription factor that is upstream of the nNOS gene [ 65 , 66 ] and thus could also have influenced the production of nitric oxide. Also, neuronal nitric oxide is “necessary” to induce withdrawal of synaptic terminals on injured motor neurons by prolonged activation of the soluble guanylyl cyclase (sGC)/protein kinase G (PKG) pathway and RhoA/Rho kinase (ROCK) signaling [ 67 , 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%